2018
DOI: 10.25134/ijsm.v1i1.843
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Budaya Kerja Dan Etos Kerja Islami Terhadap Kinerja Karyawan Pada Bank Syariah Mandiri Cabang Cirebon

Abstract: Berdasarkan�data laporan Bank Syariah Mandiri tahun 2016 terdapat beberapa pengaduan nasabah mengenai pelayanannya, pengaduan tersebut diantaranya mengenai kerja CS yang lamban, marketing yang mengecewakan, kantor cabang yang sulit dihubungi, teller yang lamban dan kinerja FL� yang tidak memuaskan, tidak dapat dipungkiri� bahwasanya pelayanan yang baik sangat penting dilakukan oleh setiap karyawan BSM dengan cara meningkatkan kinerjanya. �Oleh karena itu apabila budaya kerja dan etos kerja islami berjalan deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
2
5
0
2
Order By: Relevance
“…Kusumawati (2015) quantitatively found a result that there was a positive effect between Islamic work ethics and Islamic work performance in lecturers and employees at Universitas Islam Sultan Agung, Semarang. Some other studies also found the Islamic work ethics influenced employee performance (Mauliza, Yusuf & Ilhamsyah, 2016;Citra, Purwadi & Hakim, 2018;Layaman & Maya, 2018;Indica, 2016). Meanwhile, a study conducted by Shafissalam and Azzuhri (2016) found that Islamic work ethics did not affect employee performance.…”
Section: The Influence Of Islamic Leadership and Islamic Work Ethics On Employee Performance Of Islamic Banks In Riau Province Mediated Bmentioning
confidence: 90%
“…Kusumawati (2015) quantitatively found a result that there was a positive effect between Islamic work ethics and Islamic work performance in lecturers and employees at Universitas Islam Sultan Agung, Semarang. Some other studies also found the Islamic work ethics influenced employee performance (Mauliza, Yusuf & Ilhamsyah, 2016;Citra, Purwadi & Hakim, 2018;Layaman & Maya, 2018;Indica, 2016). Meanwhile, a study conducted by Shafissalam and Azzuhri (2016) found that Islamic work ethics did not affect employee performance.…”
Section: The Influence Of Islamic Leadership and Islamic Work Ethics On Employee Performance Of Islamic Banks In Riau Province Mediated Bmentioning
confidence: 90%
“…Factors for achieving good governance and job satisfaction include organizational citizenship behavior (OCB), and transformational leadership style, as well as work ethic for employees. This fact is based on the results of previous studies on good governance, job satisfaction, organizational citizenship behavior (OCB), transformational leadership style, and work ethic, among others the results of studies by Renggani & Wika (2014), Ferdinan (2015, Ramona, et al (2017), Chalida, et al (2015 and Layaman and Maya (2018) explaining that job satisfaction affects employee performance; Chamdan's ( 2013) study revealed that OCB affects organizational performance; study results of Royhul et al (2019) explain that transformational leadership style affects job satisfaction and organizational performance; the study results by Biatna Dulbert Tampubolon ( 2007) explain that the work ethic affects employee performance; the study results by Edi and Wiwik (2010) explains that OCB affects employee job satisfaction; the study results by Fairico, et al (2018) explain that OCB affects employee performance; study results by Mariman (2014) explain that OCB has an effect on improving individual performance in the public sector; study results by Titisari, et al (2016) explain that the work ethic affects the company's performance; Lusiana's (2017) study results explain that improving employee performance can contribute to the achievement of good governance; the study results by Didit, et al, (2016) explain that transformational leadership style affects job satisfaction; study results by Imam et al (2015) explains that the work ethic can increase job satisfaction. But based on previous studies there are also different relationships, among others the study results by Amilin (2016) explain that the work ethic does not affect employee performance; study results by Lusiana (2017) explain that job satisfaction does not affect work performance; study results by Beny (2013) explain that that transformational leadership style has no effect on job satisfaction.…”
Section: Introductionmentioning
confidence: 96%
“…Sunanda [18] stated that Islamic leadership has a positive effect on performance. The research of Sunanda Sunanda [18] is in line with Hidayatulloh [17], Layaman and Jumalia [19], Jumaing et al [20]. H1: Islamic leadership has a positive effect on employee performance e. Islamic Work Ethic The Islamic work ethic is defined as a personality attitude that forms a deep belief that working is not only to glorify oneself but also as a manifestation of good deeds and has a very noble value of worship [3].…”
Section: Leadership Islamicmentioning
confidence: 87%
“…Aswadi et al [3] shows that Islamic work ethic has a positive influence on employee performance. Research Aswadi et al [3] supported by Layaman and Jumalia [19], Dharma and Ikhsan [21], and Jufrizen et al [22].…”
Section: Leadership Islamicmentioning
confidence: 99%